2014
DOI: 10.2174/1389201015666140717090755
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive and Anti-leukemic Effects of Ethanol Extracts of Moringa oleifera Leaves on Wistar Rats Bearing Benzene Induced Leukemia

Abstract: Pharmacological exploitation of natural compounds has continued to lead to development of non-synthetic and non-toxic anticancer agents that are promising at ameliorating the menace of neoplastic diseases such as leukemia. This study is an attempt to determine the chemopreventive and antileukemic activities of ethanol extracts of Moringa oleifera leaves on benzene induced leukemia bearing rats. Leukemia was induced by intravenous injection of 0.2 mL benzene solution 48 hourly for 4 weeks in appropriate rat gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…A significant increase in WBC with a decrease in relative neutrophils was reported previously [3]. Similarly, Akanni et al [45] reported that the mean WBC and number of lymphocytes of leukaemic rats induced with benzene carcinogen were significantly higher than those of the control group. The findings of this research were supported further by the report of Law et al [32], where intraperitoneal administration of ENU induced a mixed type of leukaemia 4-7 months post injection; the leukaemia was predominantly lymphoblastic in nature.…”
Section: Discussionsupporting
confidence: 68%
“…A significant increase in WBC with a decrease in relative neutrophils was reported previously [3]. Similarly, Akanni et al [45] reported that the mean WBC and number of lymphocytes of leukaemic rats induced with benzene carcinogen were significantly higher than those of the control group. The findings of this research were supported further by the report of Law et al [32], where intraperitoneal administration of ENU induced a mixed type of leukaemia 4-7 months post injection; the leukaemia was predominantly lymphoblastic in nature.…”
Section: Discussionsupporting
confidence: 68%
“…For example, the water extract of M. oleifera leaves is known to inhibit growth and induce apoptosis in lung cancer [ 14 ], liver cancer [ 15 ], oral cancer [ 29 ], pancreatic cancer [ 17 ], esophageal cancer [ 30 ], Ehrlich ascites carcinoma [ 31 ], and human melanoma cells [ 32 ]. The alcohol extract of M. oleifera leaves can inhibit cell growth and induce apoptosis and cell cycle arrest in breast cancer, colon cancer [ 33 ], leukemia [ 16 ], and cervical cancer [ 18 ] cells. The methanolic extract of M. oleifera leaves can inhibit cell growth and induce apoptosis and cell cycle arrest in cervical cancer [ 34 ] and prostate cancer [ 35 ] cells.…”
Section: Discussionmentioning
confidence: 99%
“…M. oleifera extracts possess anti-inflammatory [ 4 ], cardioprotective [ 5 ], hypocholesterolemic [ 6 ], antidiabetic [ 7 ], antihypertensive [ 8 , 9 ], neuroprotective [ 10 ], hepatoprotective [ 11 ], antioxidant [ 12 ], and antibacterial properties [ 13 ], among others. Additionally, various parts of the M. oleifera plant, including the leaves, stem bark, fruit pods, and seeds, have growth inhibitory effects in various types of tumor cells, including lung cancer [ 14 ], liver cancer [ 15 ], leukemia [ 16 ], pancreatic cancer [ 17 ], and cervical cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high doses of the extract, particularly 2,000 mg/kg, did not exert toxicity on the tested mice. Akanni et al ( 2014 ) reported that an ethanol extract of M. oleifera leaves exhibited antileukemic activity against benzene-induced leukemic Wistar rats. The extract normalized the leukemic condition, increased GSH, and reduced MDA levels in the rats.…”
Section: Biological Activitiesmentioning
confidence: 99%